Research on a Shared Bicycle Deposit Management System Based on Blockchain Technology - Daozhi Zhao; Di Wang; Baosen Wang (Journal of Advanced Transportation)
As a green travel mode, bike sharing is developing rapidly across China. At present, charging deposits from users is the common operation mode adopted by shared bicycle enterprises. The large number of shared bicycle enterprises generates fierce market competition, and the eliminated enterprises always refuse to return user deposits. Even regular running enterprises still have trouble with the immediate return of deposits. This situation severely affects the reputation of shared bicycle enterprises, and concerns have been shared widely across the society. Meanwhile, there is a general expectation among users that their deposits could be refunded timely and a broad appeal for technical management to resolve this problem. This article uses blockchain technology to reform the current management mode for shared bicycle deposits and constructs a decentralized, user information and deposit visualized, and multidimensional supervised management system. The proposed management system makes the real-time flow direction supervision of user deposits to be realized. Furthermore, a smart contract of shared bicycle deposits with punishment mechanism is also designed. Finally, the differences between the proposed deposit management mode and the current deposit management mode are analyzed, and a simulation experiment is conducted. In the simulation experiment, the deposit theft rate of our deposit management system is 0%, which is far better than the two existing bike deposit management systems. The results show that the outstanding advantages of the proposed deposit management mode, which include improving deposit supervision and guaranteeing user deposit security, are also conducted. This article has made effective technical management exploration to reduce deposit management risks and improve deposit management institutions for shared bicycles. It has important practical reference value for accelerating the sustainable development of shared bicycle enterprises.